Patterned Arrangements of Olfactory Receptor Gene Expression in Zebrafish are Established by Radial Movement of Specified Olfactory Sensory Neurons - Xalid Bayramli (Nature Portfolio, 2017)
Abstract Spatial restriction of olfactory receptor (OR) gene expression in peripheral sense organs is a common phenomenon across species, suggesting that zonal OR expression somehow contributes to olfactory function. In zebrafish OR expression patterns reminiscent of zones occur as concentric domains with preferred diameters for different ORs. However, the function and the developmental origin of the pattern are unknown. Here we investigate olfactory sensory neuron (OSN) neurogenesis in the adult zebrafish olfactory epithelium (OE) to understand how the zonally organized OR pattern is established and maintained during the lifetime of the animal. We find that OSNs are generated from two discontinuous proliferation zones located at the central and peripheral edge of the sensory OE. OSNs turn on OR expression soon after they exit mitosis and invade the sensory tissue, approaching each other from both ends of the OE. Biased generation of OSN subpopulations at both neurogenic sites and elimination of OSNs along their route across the OE generates the impression of OR-specific expression domains. We formulated a simple mathematical model based on exact parameters derived from our analysis of OSN neurogenesis, which accurately generates OR-like distributions without the need to invoke molecular signals to pattern the OE.